1945
DOI: 10.5254/1.3546733
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Properties of Rubber and GR-S

Abstract: A new electrostatic modulator has been described for measuring the electrostatic charges on rubber, synthetic rubber, and various materials. In this apparatus the electrostatic lines of force established between the charged specimen and a stationary electrode plate connected to the grid of an audiofrequency amplifier are cut or modulated at audiofrequency by a small four-bladed, motor-driven fan. This produces in effect an alternating current voltage which can be readily amplified by the audio amplifier and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1952
1952
1953
1953

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Havenhill, Carlson, Emery, and Rankin (122,123) described a new electrostatic probe and associated equipment for detecting and recording both the polarity and magnitude of electric charges formed when rubber batches are mixed in a Banbury mixer. These contact potentials produce strong electrostatic fields from which one may obtain fundamental information on the mastication, incorporation, and dispersion of softeners and pigments.…”
Section: Aging and Deteriorationmentioning
confidence: 99%
“…Havenhill, Carlson, Emery, and Rankin (122,123) described a new electrostatic probe and associated equipment for detecting and recording both the polarity and magnitude of electric charges formed when rubber batches are mixed in a Banbury mixer. These contact potentials produce strong electrostatic fields from which one may obtain fundamental information on the mastication, incorporation, and dispersion of softeners and pigments.…”
Section: Aging and Deteriorationmentioning
confidence: 99%
“…Havenhill and coworkers (116) describe electrical test equipment for evaluating rubber and associated materials. They found that electric charges are specific for each ingredient, and by means of an electric charge recorder they can follow the breakdown of the rubber, the state of incorporation of pigments, oils, and other ingredients during mixing in an internal mixer without disturbing the operation.…”
Section: Electrical Propertiesmentioning
confidence: 99%